2013
DOI: 10.1002/jcb.24611
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy stimulates apoptosis in HER2‐overexpressing breast cancers treated by lapatinib

Abstract: HER2-overexpressing breast cancers often show hyperactivation of the HER2/AKT/mTOR signaling pathway. Lapatinib is an oral dual tyrosine kinase inhibitor (TKI) that targets both EGFR and HER2 to inhibit the proliferation of breast cancer cells. However, it is obscure whether and how lapatinib could induce autophagy in breast cancer cells, an important cell response with drug treatment. In this study, we investigated the apoptosis and the autophagy in the HER2-overexpressing breast cancer cells BT474 and AU565 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 28 publications
(29 reference statements)
1
27
0
Order By: Relevance
“…Detection of acidic vesicular organelles with acridine orange staining Acidic vesicular organelles (AVO), as marker of autophagy, were detected by acridine orange (AO) flow cytometry as described previously (14). To quantify the development of AVOs, cells were stained with 1 mg/mL of AO for 15 minutes and were then removed from the plate with trypsin-EDTA and collected for flow cytometric analysis.…”
Section: Immunofluorescencementioning
confidence: 99%
“…Detection of acidic vesicular organelles with acridine orange staining Acidic vesicular organelles (AVO), as marker of autophagy, were detected by acridine orange (AO) flow cytometry as described previously (14). To quantify the development of AVOs, cells were stained with 1 mg/mL of AO for 15 minutes and were then removed from the plate with trypsin-EDTA and collected for flow cytometric analysis.…”
Section: Immunofluorescencementioning
confidence: 99%
“…First, AMPK, activated by lapatinib, is a robust regulator of autophagy. Consistent, lapatinib activates autophagy in breast cancer cells [67] and leukemic cells [68], whereas this has not been reported for trastuzumab. Second, recent work has revealed that HER-2 physically interacts with Beclin 1 in breast cancer cells, although the biological significance of this interaction is unclear [69].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…An autophagy inhibitor, 3-Methyladenine, attenuated autophagy induced by lapatinib in a study using BT474 cells [32]. Other studies have shown that autophagy was an important mode of cell death following lapatinib treatment [33, 34].…”
Section: Discussionmentioning
confidence: 99%